Validation and psychometric properties of Bahasa Malaysia version on Parent Emotional Style Questionnaire (PESQ) - Ab Ghaffar, Siti Fatimah; Ibrahim, Mazne; Mat Yussof, Nur Dalila; Muhammad, Nur Hafizah; Musa, Ramli; Mohamad Isa, Irma Izani; Masiran, Ruziana (Springer Nature, 2024)
Abstract Currently, there are only a limited number of validated questionnaires in Bahasa Malaysia (BM) that assess parental emotional style. The objective of this study was to determine the psychometric characteristics of the BM version of the Parent Emotional Style Questionnaire (PESQ). BM was used for back-to-back translation, and exploratory factor analysis was employed to establish its construct validity. A purposive sampling method was used to select 150 respondents from a primary school in Kota Bharu, Kelantan. These respondents were chosen to represent Malay parents and to ensure the reliability and validity of the questionnaire. The BM PESQ demonstrated strong internal consistency for both emotion coaching and motiondismissing techniques, with Cronbach’s alpha coefficients of 0.85 and 0.88, respectively. Furthermore, all of the items exhibited favorable factor loading values ranging from 0.39 to 0.78. Among the 21 items, 20 items demonstrated a noteworthy contribution to their respective domains, indicating exceptional convergence values. The BM PESQ has been precisely and adequately translated into Bahasa Malaysia, and it possesses outstanding psychometric properties. Further investigation is necessary to substantiate these findings.